COMPARATIVE ANALYSIS OF THE PHYTOCHEMICAL COMPOSITION OF THE ABOVE GROUND PART OF RHODIOLA LINEARIFOLIA BORISS PLANTS. FROM DIFFERENT ECOPOPULATIONS OF THE ZAILI ALATAU (Eurasian Journal of Ecology, 2025)
Climatic conditions have a significant impact on the pharmacological activity of medicinal plants, causing quantitative and qualitative changes in the composition of biologically active substances (BAS). Temperature, humidity, light levels and other environmental factors can change the metabolic pathways of plants, which affects the production of secondary metabolites - key compounds that determine the therapeutic potential of herbal medicines. In different geographical zones and cultivation conditions, the concentrations of biologically active substances can vary significantly, which is the result of the plant’s adaptive response to environmental stress. Therefore, it is important not only to determine the amount of valuable metabolites, but also to take into account the conditions affecting their synthesis and accumulation. For the study, samples of R. Linearifolia in the flowering phase were selected from two Eco populations growing at the same altitude above sea level in the Kimasar and Butakovka gorges. An analysis of the phytochemical components of Rhodiola linearifolia extracts was carried out and possible environmental and microclimatic factors that influenced the significant difference in their phytochemical composition were analyzed. The results obtained in the course of this work are important for a better understanding of the adaptive mechanisms occurring in populations of R. linearifolia, for choosing optimal growing conditions for the species in order to develop strategies for preserving this species in natural conditions, as well as for developing an effective strategy for optimizing the conditions for the future introduction of this species without loss of pharmacologically valuable properties.Key words: ecopopulation, microclimatic factors, phytochemistry, introduction, adaptation